Vascular Delivery of Allogeneic MuStem Cells in Dystrophic Dogs Requires Only Short-Term Immunosuppression to Avoid Host Immunity and Generate Clinical/Tissue Benefits - Judith Lorant; Thibaut Larcher; Nicolas Jaulin; Benoît Hedan; Aurélie Lardenois; Isabelle Leroux; Laurence Dubreil; Mireille Ledevin; Hélicia Goubin; Sophie Moullec; Jack-Yves Deschamps; Chantal Thorin; et al. (Cell Transplantation, 2018)
Growing demonstrations of regenerative potential for some stem cells led recently to promising therapeutic proposals for neuromuscular diseases. We have shown that allogeneic MuStem cell transplantation into Golden Retriever muscular dystrophy (GRMD) dogs under continuous immunosuppression (IS) leads to persistent clinical stabilization and muscle repair. However, long-term IS in medical practice is associated with adverse effects raising safety concerns. Here, we investigate whether the IS removal or its restriction to the transplantation period could be considered. Dogs aged 4–5 months old received vascular infusions of allogeneic MuStem cells without IS (GRMD MU/no-IS ) or under transient IS (GRMD MU/tr-IS ). At 5 months post-infusion, persisting clinical status improvement of the GRMD MU/tr-IS dogs was observed while GRMD MU/no-IS dogs exhibited no benefit. Histologically, only 9-month-old GRMD MU/tr-IS dogs showed an increased muscle regenerative activity. A mixed cell reaction with the host peripheral blood mononucleated cells (PBMCs) and corresponding donor cells revealed undetectable to weak lymphocyte proliferation in GRMD MU/tr-IS dogs compared with a significant proliferation in GRMD MU/no-IS dogs. Importantly, any dog group showed neither cellular nor humoral anti-dystrophin responses. Our results show that transient IS is necessary and sufficient to sustain allogeneic MuStem cell transplantation benefits and prevent host immunity. These findings provide useful critical insight to designing therapeutic strategies.